ANALISIS KESANTUNAN BERBAHASA SISWA KELAS XI PADA PEMBELAJARAN BAHASA INDONESIA DI SMA NEGERI 13 KABUPATEN BURU - Musyawir Musyawir (Media Bina Ilmiah, 2022)
This study aims to describe the form of language politeness in class XI students in learning Indonesian at SMA Negeri 13 Buru Regency, and to describe the causes of language impoliteness in class XI students in learning Indonesian at SMA Negeri 13 Buru district. The type of research used is descriptive. The method used in this research is qualitative. The source of data in this research is student speech. The data in this study is to describe the form of politeness in the language of students when learning Indonesian. The data collection techniques in this study; recording techniques, note-taking techniques, and documentation. The results of the study show that there are six maxims in politeness in students' language when learning in class XI SMA Negeri 13 Buru Regency, namely; maxim of wisdom, generosity, humility, compatibility, praise, and sympathy. The causes of impoliteness in class XI students in learning Indonesian at SMA Negei 13, Buru Regency, namely; Internal factors, including language skills and personality possessed by a person. How is the choice of words, intonation, tone, way of pronunciation used. External factors include the family environment, peers, community environment